Molecular Sex Identification in the Hardy Rubber Tree (Eucommia ulmoides Oliver) via ddRAD Markers - Wencai Wang; Guoqian Yang; Xin Deng; Fengqing Shao; Yongquan Li; Wei Guo; Hong Liang; Xianzhi Zhang (International Journal of Genomics)
Eucommia ulmoides, also known as the industrially and medicinally important hardy rubber tree, is the sole species of Eucommiaceae. Nevertheless, its dioecious property hinders sex recognition by traditional morphological observation at very early developmental stages, thus inhibiting breeding and economic cropping. In this study, double-digest restriction site-associated DNA sequencing (ddRAD-seq) was applied to screen sex-linked molecular markers for sex identification and investigation of the sex determination system in 20 male and female E. ulmoides individual plants, respectively. In consequence, five candidate male-specific loci but no female-specific loci were predicated among the 183,752 male and 147,122 female catalogue loci by bioinformatics analysis. Subsequent PCR (polymerase chain reaction) amplification and Sanger sequencing examinations were performed on another 24 individuals, 12 for each sex, from a separate population. One ideal sex-linked locus, MSL4, was identified among the five putative male-specific loci that were found using ddRAD data. MSL4 is 479 bp in length and highly conserved in all the male individuals, suggesting its feature of being stable and repeatable. Our results also indicated that the sex of E. ulmoides is likely determined genetically. In short, this study provides a consistent and reproducible ddRAD marker (MSL4) that is able to discriminate male from female seedlings in E. ulmoides, which will be valuable for rapid breeding practice and better commercial production of this economically important tree.